Penerapan Metode Modeling dengan Media Audio Visual untuk Meningkatkan Pemahaman Rias Tari Gambyong Siswa - Ilham Rahmadhani; Adam Wahida; Surono Surono (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to improve students' understanding and skills in the makeup and costume of the Gambyong Pareanom dance through the application of the modelling method assisted by audio-visual media. The research subjects were 35 students of class X SP 5 at SMK Negeri 8 Surakarta for the 2024/2025 academic year. The research was conducted in three cycles, each consisting of planning, action, observation, and reflection stages. The learning method involved the use of videos, live demonstrations, group discussions, and independent practice. The results showed significant improvement in each cycle. In the pre-action stage, only 40% of students felt helped by the method and 68% lacked self-confidence. In Cycle I, 55% felt helped and 60% began to show better understanding. In Cycle II, with more interactive media, 72% of students felt helped and 68% reached the minimum passing grade (KKM). In Cycle III, 88% of students found the method very effective, 85% achieved the KKM, and 83% showed improved confidence. These findings prove that the modelling method using audio-visual media is effective in enhancing conceptual understanding, technical skills, and student confidence. The study recommends broader application of this method in vocational school skill-based learning to create a more engaging, contextual, and relevant learning experience aligned with workforce demands and cultural preservation.